Diferenciação abiótica do metabolismo secundário em Aspergillus aculeatus e Penicillium brasilianum utilizando sais inorgânicos - Lima, Amanda Maciel (2020)
The biosynthetic potential of microorganisms for the production of secondary metabolites is limited by the routes encoded in their genome. However, although this potential is enormous, few of them are expressed under standard cultivation conditions. As the biosynthesis of secondary metabolites of fungi occurs in response to the different chemical compositions of culture medium, in the present work studies were conducted in order to induce new metabolic routes in endophytic fungi using inorganics salts. A screening was performed by cultivating five fungal strains available in the LaBioMMi library (Penicillium brasilianum, P. brasilianum Δpal, P. brasilianum ΔNRPS 023, P. brasilianum ΔNRPS 07 e A. Aculeatus). The reference medium (Czapek control) was established to verify alterations of metabolism of fungi cultivated using seven medium modified with inorganic salts.Thus, FeSO4 concentrations were varied from 0,01 to 0,1 e 1,0 g/L; as well as FeSO4 was substituted by the other MnCl2, CoCl2, NiCl2, ZnCl2 at 0.5 g/L. The fungi were grown in triplicates of each culture condition for 14 days in static mode. After that, they were subjected to extraction from mycelium with MeOH and from fermentation broth with AcOEt. The extracts obtained were analyzed by HPLC-DAD. Thus, differences were observed in the metabolite profiles of the media extracted with AcOEt in the strains of P. brasilianum and A. aculeatus. Methanolic extracts showed metabolic differences only for A. aculeatus. After chemical analysis, the fungus A. aculeatus (LaBioMMi 481) was chosen for cultivation at larger scale, using the medium containing the halogenated salts CoCl2 and KBr.Qualitative analyrical tests were carried out evaluating the susceptibility of the fungus to different salt concentrations, optimal cultivation time in two stages of growth of the microorganism, as well as combinations of salts. The adjusted analytical parameters were used for large scale cultivation, using 6L of each medium containing 10 and 2 g/L of KBr and CoCl2, respectively, in the period of 14 days. The extracts obtained were fractionated on silica gel, under vacuum. Fractions containing apparently induced compounds were chosen for isolation by HPLC an preparative scale. The purified compounds of the fractions were analyzed by 1D and 2D NMR. Among these compounds, 7 constituents have been identified, such as RF 3192C, orlandin, kotanin, aurosperone A, fonsecinone A, pestalamide B and aspernigrin A. Pestalamide B and aspernigrin A have not yet been described as constituents produced by A. aculeatus. In addition, the biosynthesis of pestalamide B, fonsecinone A and orlandin compounds were more stimulated by medium supplemented with KBr than in the control.